Impact of the gut microbiota-Th17 cell axis on inflammatory depression - Jia, Xiuzhi; Wang, Jiayi; Ren, Dan; Zhang, Kaibo; Zhang, Hongliang; Jin, Tengchuan; Wu, Songquan (Frontiers in Psychiatry, 2024)
Depression is a serious cognitive disorder that results in significant and pervasive deficits in social behavior. These deficits can be traced back to the intricate interplay between social, psychological, and biological factors. Inflammatory depression, a treatment-resistant or non-responsive subtype of depression, may be related to the interaction between the gut microbiota and interleukin-17-producing CD4+ T cells (Th17 cells). The heterogeneity, plasticity, and effector role of Th17 cells in depression may be influenced by microbiota factors. Commensals-elicited homeostatic Th17 cells preserve the morphological and functional integrity of the intestinal barrier. In addition to pathogen-elicited inflammatory Th17 cells, commensal-elicited homeostatic Th17 cells can become conditionally pathogenic and contribute to the development of inflammatory depression. This review delves into the possible involvement of Th17 cells in inflammatory depression and examines the interplay between gut microbiota and either homeostatic or inflammatory Th17 cells.